2023
DOI: 10.1002/anie.202304908
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Polyampholyte Microgels by Depletion Flocculation and Coacervation of Nanogels in Emulsion Droplets

Abstract: In pH‐responsive drug carriers, the distribution of charges has been proven to affect delivery efficiency but is difficult to control and verify. Herein, we fabricate polyampholyte nanogel‐in‐microgel colloids (NiM−C) and show that the arrangement of the nanogels (NG) can easily be manipulated by adapting synthesis conditions. Positively and negatively charged pH‐responsive NG are synthesized by precipitation polymerization and labelled with different fluorescent dyes. The obtained NG are integrated into micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Other examples of more structurally remote monomeric sodium complexes are known in which the cation and carbanion are charge-separated. [1,2] [1] H. The authors would like to correct aspelling mistake found in the listed authors for this Research Article. Lian-Yan Hsu should be corrected to Liang-Yan Hsu in the article and the Supporting Information.…”
mentioning
confidence: 99%
“…Other examples of more structurally remote monomeric sodium complexes are known in which the cation and carbanion are charge-separated. [1,2] [1] H. The authors would like to correct aspelling mistake found in the listed authors for this Research Article. Lian-Yan Hsu should be corrected to Liang-Yan Hsu in the article and the Supporting Information.…”
mentioning
confidence: 99%